Global Trends and Hotspots in Trigeminal Neuralgia Research From 2001 to 2021: A Bibliometric Analysis - Zhu, Ganggui; Fu, Zaixiang; Su, Sheng; Tang, Yajuan; Liu, Fuyi; Yu, Wenhua (Frontiers in Neurology, 2022)
Background In recent years, there have been an increasing number of studies on trigeminal neuralgia (TN). However, a scientific and comprehensive study of the current situation and trends in the field of TN research is lacking. The purpose of this study is to summarize and visualize the development, research hotspots, and future trends in TN based on a bibliometric approach. Methods Studies on TN published from 2001 to 2021 were obtained from the Web of Science Core Collection (WoSCC). Bibliometrics, CiteSpace, and VOSviewer tools were used for bibliometric analysis and visualization. Results In total, 4,112 documents were searched. The number of research articles in the field is generally on an upward trend, with the fastest growth in the number of articles from 2017 to 2020. Shanghai Jiao Tong University, Pittsburgh University, and Mayo Clinic are the three institutions with the most publications. Shiting Li and Zakrzewska JM are the most prolific author and top co-cited authors, respectively. The Journal of Neurosurgery is the most influential journal. The top 5 keywords in that time frame are TN, microvascular decompression, facial pain, stereotactic radiosurgery, and neuropathic pain. Conclusion This is the first comprehensive scientific bibliometric analysis of the global research field on TN over the past 21 years, providing a meaningful reference for further exploration of topical issues and research trends in the field.